CHAETOMORPHA MEDIA : LOW COST BIOSORBENT FOR REMOVAL OF METHYLENE BLUE - REKHA R. DEOKAR, (International Journal of Pharma and Bio Sciences, 2016)
In the present investigation, the use of abundantly available, low-cost, highly efficient and eco-friendly biosorbent Chaetomorpha media (C.Agarth) has been reported as an alternative to the current expensive methods of removing of Methylene Blue (MB) dye from aqueous solution. The effects of different variables viz pH, agitation time, adsorbate concentration, adsorbent dose, agitation speed etc. were investigated for ascertain optimal experimental conditions. The Langmuir isotherm model has given a better conformity than the Freundlich model with 226.45 mg/g as maximum adsorption capacity at room temperature. The adsorption of MB on dried biomass of C. media was confirmed by FTIR, SEM and EDX study, as it showed the change in characterization before and after biosorption. It was found that the pseudo second order model provided a better approximation to the system’s kinetics, while intra particle diffusion study was used to furnish the mechanistic study. Present investigation and comparison with other reported adsorbents concluded that, C. media may be applied as a low-cost attractive option for removal of MB from aqueous solution.